2010
DOI: 10.1007/s11627-009-9272-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic secondary somatic embryogenesis and efficient plant regeneration in camphor tree (Cinnamomum camphora L.)

Abstract: An efficient protocol for secondary somatic embryogenesis in camphor tree is reported. Secondary somatic embryos (SSEs), initially obtained from the primary embryos of a nascent embryogenic culture in 2002, were proliferated and maintained for more than 4 yr via cyclic secondary somatic embryogenesis. Throughout this period, the embryo populations retained a high level of competence for plant regeneration. SSEs were produced on the surfaces of the cotyledons and radicular ends of maternal somatic embryos (MSEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 45 publications
(37 reference statements)
1
23
0
Order By: Relevance
“…It was observed in this study that the primary somatic embryos derived from hormone-free medium could produce secondary somatic embryos on medium without PGR, which may be beneficial for plantlet conversion, as the secondary somatic embryos maintained on medium with auxin by repetitive embryogenesis failed to complete efficient plantlet conversion with shoots and roots simultaneously. Secondary somatic embryos of C. camphora that were cultured for [4 years required a maturation treatment before germinating on a medium containing PGRs for plantlet conversion (Shi et al 2009). It was also observed in this study that the primary somatic embryos derived from hormone-free medium needed a maturation treatment before plant regeneration and secondary somatic embryogenesis could occur on medium without PGR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was observed in this study that the primary somatic embryos derived from hormone-free medium could produce secondary somatic embryos on medium without PGR, which may be beneficial for plantlet conversion, as the secondary somatic embryos maintained on medium with auxin by repetitive embryogenesis failed to complete efficient plantlet conversion with shoots and roots simultaneously. Secondary somatic embryos of C. camphora that were cultured for [4 years required a maturation treatment before germinating on a medium containing PGRs for plantlet conversion (Shi et al 2009). It was also observed in this study that the primary somatic embryos derived from hormone-free medium needed a maturation treatment before plant regeneration and secondary somatic embryogenesis could occur on medium without PGR.…”
Section: Discussionmentioning
confidence: 99%
“…3c), could be inhibited by the addition of ABA (Shi et al 2009). Germination of maturation treated somatic embryos under light or in darkness (Fig.…”
Section: Somatic Embryo Proliferation and Plantlet Regenerationmentioning
confidence: 97%
See 2 more Smart Citations
“…Shi et al (2010) also reported that secondary somatic embryos in camphor tree (Cinnamomum camphora) were produced on the surfaces of the cotyledons and radicular ends of maternal somatic embryos. According to Raemakers et al (1995), cells that were capable of direct somatic embryogenesis were physiologically similar to those in zygotic embryo.…”
Section: Anatomical Observationmentioning
confidence: 97%